Marker-assisted selection:A smart biotechnological strategy for modern plant breeding - Shruti Shrestha (Universidad Nacional Agraria La Molina, 2020)
Plant breeders and geneticists use molecular marker-assisted selection also called as MAS as a useful approach for breeding of plant to make selection more efficient and speed up the breeding cycle. MAS can be more efficient, effective, and reliable than phenotypic selection.  Molecular markers are useful to identify the economically important traits in the breeding population for further manipulation in a short time. Due to the applicability of markers at the seedling stage ensuring high precision at the reduced level of cost, marker-assisted selection offer the chances to improve responses from selection. The MAS using DNA level polymorphism accelerate the pace of selection. The main marker technologies applied are chiefly co-dominant markers i.e. microsatellite markers/SSR (Simple Sequence Repeats) marker, RFLP (Restriction Fragment Length Polymorphism) marker and SNPs (Single nucleotide polymorphisms). This review overviews the various MAS technologies and their applications in crop improvement programs.